Pressure Necrosis Requiring Fasciotomy After Kratom Overdose. Issue 2 (17th March 2022) - Tobarran, Natasha; Wolf, Carl; Cumpston, Kirk L.; Wills, Brandon K.
Abstract : Introduction: Kratom ( Mitragyna speciosa ) is a popular plant-based extract that has dose-dependent stimulatory and sedative effects. It has been used for self-treatment of opioid withdrawal and can result in seizures, hepatotoxicity, and infectious complications from bacterial contamination. Reports of morbidity and mortality associated with Kratom may be confounded by coingestants. We report a case of severe rhabdomyolysis and pressure necrosis leading to fasciotomy in a patient who was using Kratom. Case report: A 31-year-old male with substance use presented to the emergency department after loss of consciousness for 6 hours after smoking Kratom. He was found to have rhabdomyolysis, acute renal and hepatic injury, and electrolyte disturbances. No ethanol was detected, and urine drug screen was negative. Over the next 3 hours, the patient developed signs of compartment syndrome and he was transferred to the operating room for fasciotomy. He required continuous renal replacement therapy for 48 hours and his labs and clinical status improved. He was discharged 18 days later. A serum and urine sample from the first day of presentation were analyzed for mitragynine and 7-hydroxymitragynine using an Ultra Performance Liquid Chromatography-Tandem Mass Spectrometer (UPLC-MSMS) method. The serum mitragynine was 5 ng/mL and the urine mitragynine 6 ng/mL. Conclusions: Although there are numerous reports of opioids resulting in prolonged periods of immobilization and rhabdomyolysis, this is not commonly reported in Kratom overdoses. This case report highlights the profound sedative effect of Kratom and the potential of pressure necrosis injury resulting in rhabdomyolysis and compartment syndrome requiring fasciotomy.